Meningkatkan Hasil Belajar Matematika Dengan Penerapan Model Pembelajaran Inquiri Learning Dengan Bantuan LKS Di Ponpes Al-Yusufiah - Nur Atika Lubis; Haritsah Hammamah Harahap; Andi Saputra Mandopa (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2024)
This research aims to determine the direct influence of the Inquiry Learning learning model to improve Mathematics learning outcomes for class VII Al-Yusufiah Huta Holbung Islamic Boarding School. The research method used is classroom action research using two cycles carried out in the second semester with material about lines and angles. The population in this study was 29 class VII students at the Al-Yusufiah Huta Holbung Islamic Boarding School. The class used as a sample is class VII-I of the Al-Yusufiah Huta Holbung Islamic Boarding School which will use the Inquiry Learning method assisted by student worksheets (LKS) in learning. The ability of students' learning outcomes in mathematics learning in class VII-I of the Al-Yusufiah Huta Holbung Islamic Boarding School on lines and angles in the first cycle increased by 55% with the